Numerical modelling of the volcanic plume dispersion from the hydrothermal system of La Soufrière de Guadeloupe - Rave-Bonilla, Yuly Paola; Jessop, David E.; Moune, Séverine; Garbin, Céline; Moretti, Roberto (Volcanica, 2023)
Passive volcanic degassing results in the emission of toxic gases such as H2S at quasi-steady rates over long periods of time that pose a significant hazard to human health even in low gas concentrations. Currently, La Soufrière de Guadeloupe has one of the highest gas emission rates in the Lesser Antilles arc, with gas emitted mainly from low-temperature fumaroles. In this study, gas dispersion from the volcano between 2016–2021 was modelled using a numerical code that takes into account wind and atmospheric data, topography and gas flux measurements. We ran c.100 individual simulations of the most frequently observed wind and gas flux conditions using a Monte-Carlo scheme. Our results, validated using air-quality measurements and citizen-science surveys, show that the most exposed zones are the hamlet of Matouba and the upper St. Claude. These areas have 20% and 5% probability, respectively, of exceeding H2S guidelines for long-term gas exposure (70 ppb).